Makna Filosofi “Sega Golong” sebagai Bentuk Kebulatan Tekad dalam Serat Babad Bendaran - Egita Fitri Nur Hayati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
The article titled “The Philosophical Meaning of ‘Sega Golong’ as a Form of Resolve in the Serat Babad Bendaran” aims to explain the philosophy of sega golong as a form of resolve and to describe the various forms of resolve found in the Serat Babad Bendaran as a reflection of the sega golong philosophy. This study falls under philological research, drawing its primary data from the Serat Babad Bendaran. It employs Kutha Ratna’s theory of literary anthropology. Data collection was conducted using literature review and textual analysis methods. The research methodology employed is qualitative descriptive. This study reveals that the philosophy of sega golong, as a form of resolve, is an effort or inner drive within an individual to achieve specific life goals. There are five forms of resolve in the Serat Babad Bendaran, namely courage, hard work, perseverance and initiative, and discipline. It is hoped that these forms of resolve can serve as examples in the pursuit of human life goals.